Metal matrix composites synthesis, wear characteristics, machinability study of MMC brake drum - Natarajan, Nanjappan; Krishnaraj, V. (Vijayan); Davim, J. Paulo (Springer International Publishing, 2015)
This book is dedicated to composite materials, presenting different synthesis processes, composite properties and their machining behaviour. The book describes also the problems on manufacturing of metal matrix composite components. Among others, it provides procedures for manufacturing of metal matrix composites and case studies.